REVIEW OF FATIGUE LIFE EVALUATION FOR HELICOPTER COMPOSITE BLADES - MA CunWang; LI GuangLiang; QU BaoJie (Jixie qiangdu)
Rotor blades are one of the most important parts of helicopter,and its can be used as lifting surface,pulling surface and control surface in flight. The fatigue life evaluation of rotor blades is the very important problem in helicopter engineering development. The history on fatigue life evaluation for helicopter composite blades is simple reviewed in this paper.Then,the main methods of fatigue life evaluation for composite blades are introduced in detail,including to damage tolerance method,flaw tolerance method and its flow chart,practical application,key problems etc. Furthermore,aim to the practical engineering application,existing problems in the three methods are analysed in-depth. Next,the unconventionality fatigue life evaluation methods are introduced,including to residual strength method,progressive damage method,the method based on dynamic characteristic,and the examples of these methods are presented. At last,based on personal knowledge,the authors summarize some thinking to the fatigue life prediction for composite blades,and these thinking is perhaps helpful to related researcher.